Intubation Ergonomics and Effectiveness using Aerosol Box - Shaik Farid Abdull Wahab; Rohayu Othman; Ahmad Rasdan Ismail (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 03-2021) [August 2021]